Multipath Local Error Management Technique Over Ad Hoc Networks - Panahi, Pejman (IEEE Computer Soc, 2008)
Nowadays wireless networks are as an important and wide usage part of communication world. Flexible nature of Ad Hoc networks and ability of them for using in different situations makes them a suitable option for using in territories suffering lack of established structure based networks. Transmitting video over ad hoe networks due to it's dynamic nature and properties of video packets makes a lot of challenges. The key idea of proposed schema is based on sending video packets over two disjoint paths beside using buffering technique in special nodes of network. In each of every path there is only one node selected as proxy node. The main task of these nodes is summarized as local error management while transferring packets among nodes to overcome high loss rate of video packets so received video at target will have better quality.
4th International Conference on Automated Solutions for Cross Media Content and Multi-Channel Distribution -- NOV 17-19, 2008 -- Florence, ITALY
Keywords: Disjoint Ad Hoc Paths; Multipath video Transferring; Buffering technique; Local Error Management; Video Proxy Nodes